Payment for ecosystem services (pes) in watershed area: Bintang Hijau Forest Reserve, Perak - Samdin, Zaiton; Tuan Ibrahim, Tuan Marina; Abdul Hamid, Hazandy (Forestry Department Peninsular Malaysia, 2020)
PES is an innovative mechanism for ensuring and enhancing the provision of ecosystem goods and services through the transfer of financial resources. The basic concept of PES is that those who benefit from ecosystem services should pay damages or rewards to those who provide a service. One of the main features of PES is a voluntary transaction. This study focused on Air Masyarakat; one of the most important watershed products in Bintang Hijau Forest Reserve, Perak. The area was chosen based on its importance and it has a great impact on the local community. It is to provide a PES mechanism option guideline for the Air Masyarakat services in Bintang Hijau Forest Reserve which involved users of Air Masyarakat (local community) and water supply agencies (Lembaga Air Perak). This mechanism is established to ensure financial sustainability to cover the costs involved in managing and conserving Bintang Hijau Forest Reserve. The mechanism will be a source of reference and guidance to responsible parties such as the State Forestry Department to manage the watershed area more efficiently and sustainably.